Improving consumer stickiness in livestream e-commerce: A mixed-methods study - Shen, Lihong; Zhang, Yuning; Fan, Ying; Chen, Yiduo; Zhao, Yi (Frontiers in Psychology, 2022)
With the continuous development and improvement of Internet media technologies in China, the influence of livestream e-commerce is becoming increasingly prominent, and an increasing number of people are engaging in consumption activities in this field. It is important to study consumer stickiness in livestream e-commerce to promote economic structure adjustment and innovation-driven development. Therefore, in this study, we adopted the expectation confirmation theory as the theoretical framework and analysed the expectation confirmation theory and stickiness. The study considered satisfaction as the previous influencing factor of user and consumer stickiness, replaced the continuance intention in the expectation confirmation model with consumer stickiness as the explanatory variable, introduced the variable of perceived playfulness as the value perception after user experience, and established a consumer stickiness factors model. A total of 262 valid questionnaires were collected in this study, and SmartPLS analysis along with interviews were used to justify the limitations of data analysis. The results of the study demonstrated a significant effect of perceived usefulness and confirmation on satisfaction, a significant effect of confirmation on perceived usefulness, a significant effect of satisfaction on stickiness, and a significant effect of confirmation on perceived playfulness. Based on findings from the data analysis and interviews, we further proposed rationalized recommendations, and aimed to provide some theoretical guidance for future research on live streaming.